Landasan Historis Pendidikan Islam: Klasik-Modern dan Tokoh Pendidikan Islam & Barat - Syahida Ajrina; Syaifuddin Sabda (YASIN, 2026)
Islamic education is one of the educational systems with deep historical roots since the early development of Islam and has undergone dynamic transformations in line with the evolution of Islamic civilization over time. This study aims to examine and analyze the historical foundations of Islamic education from the classical to the modern period, as well as to review the thought of key Islamic and Western educational figures who have influenced educational development. This research is a literature study employing a qualitative approach with a library research design that examines, reviews, and analyzes literature sources in the form of books, journals, and research articles related to the historical foundations of Islamic education (classical–modern) and Islamic–Western educational thinkers. The findings show that the historical foundations of Islamic education have experienced significant growth and development that can be mapped into three major periods: (1) the classical period (650–1250 CE), when Islamic education was carried out through the dakwah of Prophet Muhammad (peace be upon him) and his Companions; (2) the middle period (1250–1800 CE), when various aspects of life in the Islamic world, including education, reached a golden age; and (3) the modern period (1800 CE–present), when Islamic education has developed rapidly through integration with Western sciences and technology. In addition, this study identifies key figures in the Islamic educational tradition, such as Ibnu Sina, Al-Farabi, Al-Ghazali, Ibnu Khaldun, and Al-Khawarizmi, as well as Western educational thinkers such as Jean Piaget, John Locke, Maria Montessori, Friedrich Froebel, and John Dewey, who have contributed to shaping educational discourse and practice. The study concludes that a comprehensive understanding of the historical foundations and the thought of Islamic and Western educational figures is essential for enriching the development of contemporary Islamic educational theory and practice, particularly in formulating educational models that are responsive to contemporary demands while remaining firmly rooted in the Islamic scholarly tradition.